Effect of applying lactic acid bacteria and propionic acid on fermentation quality and aerobic stability of oats‐common vetch mixed silage on the Tibetan plateau. (11th December 2014) - Zhang, Jie; Guo, Gang; Chen, Lei; Li, Junfeng; Yuan, Xianjun; Yu, Chengqun; Shimojo, Masataka; Shao, Tao
Abstract The objective of this study was to evaluate effects of lactic acid bacteria and propionic acid on the fermentation quality and aerobic stability of oats‐common vetch mixed silage by using a small‐scale fermentation system on the Tibetan plateau. (i) An inoculant (Lactobacillus plantarum) (L) or (ii) propionic acid (P) or (iii) inoculant + propionic acid (PL) were used as additives. After fermenting for 60 days, silos were opened and the aerobic stability was tested for the following 15 days. The results showed that all silages were well preserved with low pH and NH3‐N, and high lactic acid content and V‐scores. L and PL silages showed higher (P < 0.05) lactic acid and crude protein content than the control silage. P silage inhibited lactic acid production. Under aerobic conditions, L silage had similar yeast counts as the control silage (> 105 cfu/g fresh matter (FM)); however, it numerically reduced aerobic stability for 6 h. P and PL silages showed fewer yeasts (< 105 cfu/g FM) (P < 0.05) and markedly improved the aerobic stability (> 360 h). The result suggested that PL is the best additive as it could not only improved fermentation quality, but also aerobic stability of oats‐common vetch mixed silage on the Tibetan plateau.